Diagnostic and therapeutic efficacy of urinary bladder hydrodistension in patients with bladder pain syndrome - Коšević Branko; Nikolić, Ivica; Jovanović, Mirko; Spasić, Aleksandar (Vojnosanitetski pregled, 2024)
Background/Aim. Interstitial cystitis (IC)/bladder pain syndrome (BPS) is a condition with recurring discomfort or pain in the urinary bladder and the surrounding pelvic region without an identifiable disease. The aim of this study was to assess hydrodistension as a diagnostic and treatment procedure in patients with BPS. Methods. This prospective study included 45 patients who underwent cystoscopy with hydrodistension. The mean values for 24-hr voiding frequency, maximal voided urine volume, average voided urine volume, and minimal voided urine volume originated from the frequency volume chart. The values were compared between the time before hydrodistension and one, three, and six months after that. Results. By comparing the initial data and data in all three follow-up periods (after 1, 3, and 6 months), the statistical significance (p < 0.046) was found, and that: for 24-hr voiding frequency, it was 19.64 ± 3.56, 9.42 ± 1.71, 9.58 ± 1.45, and 12.2 ± 2.79, respectively; then, for the minimal voided urine volume (p < 0.03), it was 59.11 ± 23.72 mL, 114.89 ± 4.09 mL, 112.44 ± 100.86 mL, and 89.00 ± 29.45 mL, respectively; for an average voided volume (p < 0.04), it was 105.33 ± 18.29 mL, 186.89 ± 23.14 mL, 186.44 ± 21.44 mL, and 155.78 ± 30.78 mL, respectively. There was no significant statistical difference (p < 0.1) regarding the maximal voided urine volume between initial and follow-up interval data: 196.89 ± 43.68 mL, 312.89 ± 54.59 mL, 316.00 ± 49.47 mL, 266.67 ± 53.17 mL, respectively. Conclusion. Our results demonstrate that hydrodistension is a reliable diagnostic and therapeutic procedure.